Infrared absorbing composite particles, infrared absorbing particle dispersion, and infrared absorbing particle dispersion
By coating tungsten oxide fine particles with a surface treatment containing hydrolysis products of metal chelate compounds and silicon compounds, the issues of water penetration and decreased infrared absorption in infrared absorbing materials are addressed, resulting in enhanced heat resistance and sustained performance.
Patent Information
- Application Number
- JP2021103089
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-22
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-06-22
AI Technical Summary
Infrared absorbing materials containing tungsten oxide fine particles face issues with water vapor and water penetration, leading to decomposition of the surface layer and a decrease in infrared absorption performance over time.
Surface-treated infrared absorbing fine particles are coated with a predetermined coating film containing hydrolysis products of metal chelate compounds and silicon compounds, which are uniformly dispersed within, on, or near the surface of the particles to enhance heat resistance and infrared absorption.
The surface-treated infrared absorbing fine particles exhibit improved heat resistance and maintain excellent infrared absorption properties, even when exposed to high temperatures and humidity, thereby extending the material's lifespan and performance.
Smart Images

Figure 0007655111000003 
Figure 0007655111000001 
Figure 0007655111000002
Abstract
Description
[Technical field]
[0001] The present invention relates to surface-treated infrared absorbing microparticles, which are infrared absorbing microparticles that transmit light in the visible light region and absorb light in the infrared region and have a surface coated with a specified coating film, and which further contain a silicon compound. [Background technology]
[0002] In recent years, the demand for infrared absorbers has been increasing rapidly, and many patents related to infrared absorbers have been proposed. Looking at these proposals from a functional perspective, for example, there are those that aim to block light in the near-infrared region while sufficiently taking in visible light in the fields of window materials for various buildings and vehicles, thereby suppressing the rise in temperature inside the room while maintaining brightness.
[0003] In Patent Document 1, the present inventors disclosed surface-treated infrared-absorbing microparticles, which are infrared-absorbing microparticles having excellent moist heat resistance and excellent infrared-shielding properties, in which the surfaces of tungsten oxide microparticles and / or composite tungsten oxide microparticles are coated with a coating film containing one or more selected from hydrolysis products of metal chelate compounds, polymers of hydrolysis products of metal chelate compounds, hydrolysis products of cyclic metal oligomer compounds, and polymers of hydrolysis products of cyclic metal oligomer compounds, and a method for producing the same. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 093524 Summary of the Invention [Problem to be solved by the invention]
[0005] According to the study by the present inventors, it was found that in an infrared absorbing material (film, resin sheet, etc.) containing the tungsten oxide microparticles and / or composite tungsten oxide microparticles, water vapor or water in the air gradually penetrates into the solid resin contained in the optical member depending on the usage conditions and method. Then, it was found that when water vapor or water gradually penetrates into the solid resin, the surface of the tungsten oxide microparticles is decomposed, the transmittance of light with a wavelength of 200 to 2600 nm increases over time, and the infrared absorbing performance of the infrared absorbing material gradually decreases. In the present invention, a solid resin refers to a polymer medium that is solid at room temperature, and is a concept that includes polymer media other than those that are three-dimensionally crosslinked (in the present invention, it may also be referred to as a "matrix resin").
[0006] Under the above circumstances, the present inventors have disclosed in Patent Document 1 surface-treated infrared-absorbing microparticles, which are infrared-absorbing microparticles having excellent moist heat resistance and excellent infrared-shielding properties, and in which the surfaces of tungsten oxide microparticles and / or composite tungsten oxide microparticles are coated with a coating film containing one or more selected from hydrolysis products of metal chelate compounds, polymers of hydrolysis products of metal chelate compounds, hydrolysis products of cyclic metal oligomer compounds, and polymers of hydrolysis products of cyclic metal oligomer compounds, as well as a method for producing the same.
[0007] However, because infrared absorbing materials are basically used outdoors due to their characteristics, they are often required to have high weather resistance. As market demands increase year by year, the infrared shielding fine particles disclosed in Patent Document 1 are also required to have heat resistance.
[0008] The present invention has been made under the above circumstances, and an object of the present invention is to provide surface-treated infrared-absorbing microparticles having excellent heat resistance and excellent infrared absorption properties, and an infrared-absorbing microparticle dispersion and an infrared-absorbing microparticle dispersion using the surface-treated infrared-absorbing microparticles. [Means for solving the problem]
[0009] In order to solve the above-mentioned problems, the present inventors have conducted research into a configuration that uses the above-mentioned surface-treated infrared absorbing particles having excellent optical properties as infrared absorbing particles and enables the heat resistance of the surface-treated infrared absorbing particles to be improved. As a result, they have come up with a configuration in which a compound capable of improving the heat resistance of the surface-treated particles is uniformly dispersed in one or more locations selected from within the coating film of the surface-treated particles, on the coating film, and near the surface.
[0010] The present inventors have continued their research and have come up with the idea that a silicon compound is a compound that improves the heat resistance of the above-mentioned surface-treated infrared absorbing nanoparticles and has excellent affinity for the coating film. As a result of further research, the inventors have come up with a method of adding the silicon compound that minimizes the effect of the silicon compound on the dispersibility of the surface-treated infrared absorbing nanoparticles and the surface-treated infrared absorbing nanoparticle dispersion.
[0011] That is, the inventors have conceived of surface-treated infrared absorbing particles, surface-treated infrared absorbing particle dispersion liquid, surface-treated infrared absorbing particle dispersion powder, and surface-treated infrared absorbing particle dispersion, which are obtained by adding a silicon compound to the surface-treated infrared absorbing particles.The inventors have also found that the surface-treated infrared absorbing particles have excellent heat resistance. Furthermore, the present inventors have found that the surface-treated infrared-absorbing microparticles, a surface-treated infrared-absorbing microparticle powder containing the surface-treated infrared-absorbing microparticles, and an infrared-absorbing microparticle dispersion produced using an infrared-absorbing microparticle dispersion liquid in which the surface-treated infrared-absorbing microparticles are dispersed in a suitable medium, all have excellent heat resistance and excellent infrared absorption properties, leading to the present invention.
[0012] That is, the first invention for solving the above-mentioned problems is: The surface of the infrared absorbing particles is Infrared absorbing composite particles coated with a coating film containing one or more selected from a hydrolysis product of a metal chelate compound, a polymer of a hydrolysis product of a metal chelate compound, a hydrolysis product of a metal cyclic oligomer compound, and a polymer of a hydrolysis product of a metal cyclic oligomer compound, The infrared absorbing composite particles have a silicon compound present in one or more locations selected from within the coating film, on the coating film, and near the surface of the infrared absorbing composite particles. The second invention is The infrared absorbing composite particles according to the first aspect of the present invention are characterized in that the coating film has a thickness of 0.5 nm or more. The third invention is The infrared absorbing composite particles according to the first or second invention are characterized in that the metal chelate compound or the metal cyclic oligomer compound contains one or more metal elements selected from Al, Zr, Ti, Si and Zn. The fourth invention is The infrared absorbing composite nanoparticles according to any one of the first to third inventions, wherein the metal chelate compound or the metal cyclic oligomer compound has one or more groups selected from an ether bond, an ester bond, an alkoxy group, and an acetyl group. The fifth invention is The infrared absorbing composite fine particles according to any one of the first to fourth aspects of the present invention are characterized in that the silicon compound is silica fine particles. The sixth invention is The infrared absorbing composite particles according to any one of the first to fifth aspects of the present invention are infrared absorbing composite tungsten oxide particles represented by the general formula MxWyOz (wherein M is one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, I, and Yb, W is tungsten, and O is oxygen, 0.001≦x / y≦1, 2.0≦z / y≦3.0). The seventh invention is The infrared absorbing composite particles according to any one of the first to sixth aspects of the present invention have a carbon concentration of 0.2% by mass or more and 5.0% by mass or less. The eighth invention is The infrared absorbing composite particles according to any one of the first to seventh aspects of the present invention are dispersed in a liquid medium to form an infrared absorbing particle dispersion. The ninth invention is In the infrared absorbing nanoparticle dispersion according to an eighth aspect of the present invention, the liquid medium is at least one liquid medium selected from the group consisting of organic solvents, oils and fats, liquid plasticizers, compounds that are polymerized by curing, and water. The tenth invention is The infrared absorbing fine particle dispersion comprises the infrared absorbing composite fine particles according to any one of the first to seventh aspects of the present invention dispersed in a solid resin. The eleventh invention is The infrared absorbing nanoparticle dispersion according to a tenth invention, wherein the solid resin is one or more resins selected from the group consisting of fluororesin, PET resin, acrylic resin, polyamide resin, vinyl chloride resin, polycarbonate resin, olefin resin, epoxy resin, and polyimide resin. The twelfth invention is The infrared absorbing nanoparticle dispersion is a dried and solidified product of the infrared absorbing nanoparticle dispersion liquid according to the eighth or ninth invention. Effect of the Invention
[0013] By using the surface-treated infrared absorbing nanoparticles according to the present invention, it is possible to produce an infrared absorbing nanoparticle dispersion having high heat resistance and excellent infrared absorbing properties. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a schematic plan view of a crystal structure in a composite tungsten oxide having a hexagonal crystal structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present embodiment will be described in detail below in the following order: [1] infrared absorbing microparticles, [2] surface treatment agent used for surface coating of infrared absorbing microparticles, [3] method for surface coating of infrared absorbing microparticles, [4] addition of silicon compound and infrared absorbing composite microparticles, [5] method for adding silicon compound, and [6] infrared absorbing microparticle dispersion, infrared absorbing microparticle dispersion, infrared absorbing substrate, and article obtained using the infrared absorbing composite microparticles. In this embodiment, "a coating film formed on the surface of infrared absorbing fine particles using one or more selected from hydrolysis products of metal chelate compounds, polymers of hydrolysis products of metal chelate compounds, hydrolysis products of metal cyclic oligomer compounds, and polymers of hydrolysis products of metal cyclic oligomer compounds in order to impart moist heat resistance to the infrared absorbing fine particles" may be simply referred to as "coating film".
[0016] [1] Infrared absorbing particles In general, materials containing free electrons are known to show a reflection / absorption response to electromagnetic waves around the solar radiation range of wavelengths from 200 nm to 2600 nm due to plasma oscillations. It is known that when powders of such materials are made into particles smaller than the wavelength of light, the geometric scattering in the visible light range (wavelengths from 380 nm to 780 nm) is reduced, resulting in transparency in the visible light range. In this embodiment, the term "transparency" is used to mean "high transmittance with little scattering of light in the visible light region."
[0017] On the other hand, WO3 with oxygen deficiency and composite tungsten oxides in which electropositive elements such as Na are added to WO3 are known to be conductive materials with free electrons. Furthermore, analysis of single crystals of these materials with free electrons suggests the response of the free electrons to light in the infrared region. The present inventors have found that within a specific portion of the composition range of tungsten and oxygen, there exists a range that is particularly effective as infrared absorbing microparticles, and have come up with the idea of composite tungsten oxide microparticles that are transparent in the visible light region and absorb in the infrared region. Here, the composite tungsten oxide particles, which are the infrared absorbing particles according to this embodiment, will be described.
[0018] By adding element M, which will be described later, to the above-mentioned WO3 to form a composite tungsten oxide, free electrons are generated in the WO3, and strong absorption characteristics derived from the free electrons are expressed, particularly in the near-infrared region, making it effective as near-infrared absorbing nanoparticles around 1000 nm. That is, more efficient infrared absorbing particles can be obtained by combining the control of the oxygen amount with the addition of the element M that generates free electrons to the WO3. When the general formula of the infrared absorbing particles obtained by combining the control of the oxygen amount with the addition of the element M that generates free electrons is written as MxWyOz (where M is the element M, W is tungsten, and O is oxygen), it is desirable for the infrared absorbing particles to satisfy the relationships of 0.001≦x / y≦1 and 2.0≦z / y≦3.0.
[0019] First, the value of x / y, which indicates the amount of element M added, will be described. If the value of x / y is greater than 0.001, a sufficient amount of free electrons are generated in the composite tungsten oxide, and the desired infrared absorbing effect can be obtained. The more the amount of element M added, the more the supply of free electrons increases, and the infrared absorbing efficiency also increases, but the effect saturates when the value of x / y is about 1. In addition, if the value of x / y is less than 1, it is preferable because it is possible to avoid the generation of an impurity phase in the infrared absorbing nanoparticles.
[0020] Furthermore, the element M is preferably one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, I, and Yb.
[0021] Here, from the viewpoint of stability in the MxWyOz to which the element M is added, the element M is more preferably one or more elements selected from alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, and Re. And, from the viewpoint of improving the optical properties and weather resistance of the infrared absorbing fine particles, the element M is more preferably an alkali metal, an alkaline earth metal element, a transition metal element, a Group 4B element, or a Group 5B element.
[0022] Next, the value of z / y that indicates the control of oxygen content will be described. Regarding the value of z / y, in the composite tungsten oxide represented by MxWyOz, the same mechanism as that of the tungsten oxide represented by WyOz described above works, and also in the case of z / y=3.0 or 2.0≦z / y≦2.2, there is the supply of free electrons due to the amount of element M added described above. Therefore, 2.0≦z / y≦3.0 is preferable, 2.2≦z / y≦3.0 is more preferable, and 2.45≦z / y≦3.0 is even more preferable.
[0023] Furthermore, when the composite tungsten oxide microparticles have a hexagonal crystal structure, the microparticles have improved transmission in the visible light region and improved absorption in the infrared region. This will be explained with reference to Fig. 1, which is a schematic plan view of the hexagonal crystal structure. In FIG. 1, six octahedra formed of WO6 units, indicated by the reference symbol 11, are assembled to form a hexagonal void, and an element M, indicated by the reference symbol 12, is arranged in the void to form one unit, and a large number of these units are assembled to form a hexagonal crystal structure. In order to obtain the effect of improving light transmission in the visible light region and improving light absorption in the infrared region, it is sufficient that the composite tungsten oxide microparticles contain the unit structure described with reference to FIG. 1, and the composite tungsten oxide microparticles may be crystalline or amorphous.
[0024] When the cations of element M are added to the hexagonal gaps, the transmission of light in the visible light region is improved, and the absorption of light in the infrared region is improved. Generally, the hexagonal crystal is easily formed when an element M with a large ionic radius is added. Specifically, the hexagonal crystal is easily formed when Cs, K, Rb, Tl, In, Ba, Li, Ca, Sr, Fe, or Sn is added. Of course, elements other than these may be used as long as the above-mentioned element M is present in the hexagonal gaps formed by the WO6 units, and the elements are not limited to the above-mentioned elements.
[0025] When the composite tungsten oxide microparticles having a hexagonal crystal structure have a uniform crystal structure, the amount of the added element M is preferably 0.2 or more and 0.5 or less, more preferably 0.33, in terms of the value of x / y. When the value of x / y is 0.33, it is considered that the above-mentioned element M is arranged in all of the hexagonal gaps.
[0026] In addition, tetragonal and cubic composite tungsten oxides other than hexagonal are also effective as infrared absorbing particles. The absorption position in the infrared region tends to change depending on the crystal structure, and the absorption position tends to move to the long wavelength side in the order of cubic crystal < tetragonal crystal < hexagonal crystal. In addition, the absorption in the visible light region is small in the order of hexagonal crystal, tetragonal crystal, and cubic crystal. Therefore, it is preferable to use hexagonal composite tungsten oxide for applications that transmit more light in the visible light region and block more light in the infrared region. However, the tendency of the optical characteristics described here is merely a rough tendency, and changes depending on the type of added element, the added amount, and the amount of oxygen, and this embodiment is not limited to this. The infrared absorbing particles containing composite tungsten oxide particles according to this embodiment largely absorb light in the near infrared region, particularly at wavelengths around 1000 nm, and therefore often have a transmitted color tone ranging from blue to green.
[0027] The dispersed particle size of the composite tungsten oxide particles in the infrared absorbing particles can be selected depending on the purpose of use. First, when used in applications where transparency must be maintained, it is preferable that the particle size is 800 nm or less. This is because particles smaller than 800 nm do not completely block light due to scattering, and can maintain visibility in the visible light range while efficiently maintaining transparency at the same time. In particular, when transparency in the visible light range is important, it is preferable to further consider scattering by particles.
[0028] When the reduction of scattering by the particles is important, the dispersion particle diameter is 200 nm or less, preferably 100 nm or less. The reason for this is that if the dispersion particle diameter of the particles is small, the scattering of light in the visible light region of wavelength 400 nm to 780 nm due to geometric scattering or Mie scattering is reduced, and the infrared absorbing film becomes like cloudy glass, and it is possible to avoid not being able to obtain clear transparency. That is, when the dispersion particle diameter is 200 nm or less, the geometric scattering or Mie scattering is reduced, and it becomes the Rayleigh scattering region. In the Rayleigh scattering region, the scattered light is reduced in proportion to the sixth power of the particle diameter, so that the scattering is reduced and the transparency is improved as the dispersion particle diameter decreases. Furthermore, if the dispersed particle size is 100 nm or less, the scattered light is very little, which is preferable. From the viewpoint of avoiding light scattering, the dispersed particle size is preferably small, and if the dispersed particle size is 1 nm or more, industrial production is easy.
[0029] By setting the dispersed particle diameter to 800 nm or less, the haze value of the infrared absorbing nanoparticle dispersion in which the infrared absorbing nanoparticles according to this embodiment are dispersed in a medium can be set to 30% or less with a visible light transmittance of 85% or less. If the haze value is greater than 30%, the product becomes like cloudy glass and does not have clear transparency. The dispersed particle size of the infrared absorbing fine particles can be measured using an instrument such as ELS-8000 manufactured by Otsuka Electronics Co., Ltd., which is based on the principle of dynamic light scattering.
[0030] Furthermore, in composite tungsten oxide particles, the so-called "Magneli phase" having a composition ratio expressed as 2.45≦z / y≦2.999 is chemically stable and has good absorption characteristics in the infrared region, and is therefore preferable as infrared absorbing particles. In addition, from the viewpoint of exhibiting excellent infrared absorbing properties, the crystallite diameter of the infrared absorbing fine particles is preferably 1 nm or more and 200 nm or less, more preferably 1 nm or more and 100 nm or less, and even more preferably 10 nm or more and 70 nm or less. The crystallite diameter is measured by measuring the X-ray diffraction pattern by powder X-ray diffraction method (θ-2θ method) and analyzing by the Rietveld method. The X-ray diffraction pattern can be measured by using, for example, a powder X-ray diffractometer "X'Pert-PRO / MPD" manufactured by PANalytical, Spectris Co., Ltd.
[0031] [2] Surface treatment agent used for coating the surface of infrared absorbing particles In this embodiment, the surfaces of the infrared ray absorbing particles are coated with a surface treatment agent described below to obtain surface-treated infrared ray absorbing particles. The surface treatment agent used for coating the surface of the infrared absorbing microparticles according to this embodiment is at least one selected from hydrolysis products of metal chelate compounds, polymers of hydrolysis products of metal chelate compounds, hydrolysis products of metal cyclic oligomer compounds, and polymers of hydrolysis products of metal cyclic oligomer compounds. From the viewpoint that the metal chelate compound and the metal cyclic oligomer compound are preferably metal alkoxides, metal acetylacetonates, and metal carboxylates, they preferably have one or more groups selected from an ether bond, an ester bond, an alkoxy group, and an acetyl group.
[0032] Here, the surface treatment agent according to the present embodiment will be described in the following order: (1) metal chelate compound, (2) metal cyclic oligomer compound, (3) hydrolysis products and polymers of the metal chelate compound and metal cyclic oligomer compound, and (4) the amount of the surface treatment agent added.
[0033] (1) Metal chelate compounds The metal chelate compound used in this embodiment is preferably one or more selected from Al-, Zr-, Ti-, Si- and Zn-based chelate compounds containing an alkoxy group.
[0034] Examples of aluminum-based chelate compounds include aluminum alcoholates such as aluminum ethylate, aluminum isopropylate, aluminum sec-butylate, and mono-sec-butoxyaluminum diisopropylate, or polymers thereof, ethyl acetoacetate aluminum diisopropylate, aluminum tris(ethyl acetoacetate), octyl acetoacetate aluminum diisopropylate, stearyl acetoaluminum diisopropylate, aluminum monoacetylacetonate bis(ethyl acetoacetate), and aluminum tris(acetylacetonate). These compounds are alkoxy-containing aluminum chelate compounds obtained by dissolving aluminum alcoholate in an aprotic solvent, a petroleum solvent, a hydrocarbon solvent, an ester solvent, a ketone solvent, an ether solvent, an amide solvent, or the like, adding a β-diketone, a β-ketoester, a monohydric or polyhydric alcohol, a fatty acid, or the like to the solution, heating under reflux, and subjecting the solution to a ligand substitution reaction.
[0035] Examples of zirconia-based chelate compounds include zirconium alcoholates such as zirconium ethylate and zirconium butyrate, or polymers thereof, zirconium tributoxystearate, zirconium tetraacetylacetonate, zirconium tributoxyacetylacetonate, zirconium dibutoxybis(acetylacetonate), zirconium tributoxyethylacetoacetate, zirconium butoxyacetylacetonate bis(ethylacetoacetate), and the like.
[0036] Examples of titanium-based chelate compounds include titanium alcoholates such as methyl titanate, ethyl titanate, isopropyl titanate, butyl titanate, and 2-ethylhexyl titanate, as well as polymers thereof, titanium acetylacetonate, titanium tetraacetylacetonate, titanium octylene glycolate, titanium ethylacetoacetate, titanium lactate, and titanium triethanolamine.
[0037] As the silicon-based chelate compound, a tetrafunctional silane compound represented by the general formula: Si(OR)4 (where R is the same or different monovalent hydrocarbon group having 1 to 6 carbon atoms) or a hydrolysis product thereof can be used. Specific examples of tetrafunctional silane compounds include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, etc. Furthermore, it is also possible to apply silane monomers (or oligomers) in which a part or all of the alkoxy groups of these alkoxysilane monomers are hydrolyzed to form silanol (Si-OH) groups, and polymers self-condensed through a hydrolysis reaction.
[0038] Furthermore, hydrolysis products of tetrafunctional silane compounds (there is no appropriate terminology that indicates the entire intermediate of tetrafunctional silane compounds) include silane monomers in which a part or all of the alkoxy groups are hydrolyzed to become silanol (Si-OH) groups, oligomers of 4-5, and polymers (silicone resins) with a weight average molecular weight (Mw) of about 800 to 8000. Note that not all of the alkoxysilyl groups (Si-OR) in the alkoxysilane monomers are hydrolyzed to become silanol (Si-OH) during the hydrolysis reaction.
[0039] Preferred examples of zinc-based chelate compounds include zinc salts of organic carboxylates such as zinc octylate, zinc laurate, and zinc stearate, zinc acetylacetone chelate, zinc benzoylacetone chelate, zinc dibenzoylmethane chelate, and zinc acetoacetate chelate.
[0040] (2) Metallocyclic oligomer compounds The metal cyclic oligomer compound according to the present embodiment is preferably at least one selected from Al-, Zr-, Ti-, Si-, and Zn-based cyclic oligomer compounds. Among them, preferred examples include cyclic aluminum oligomer compounds such as cyclic aluminum oxide octylate.
[0041] (3) Hydrolysis products and polymerization products of metal chelate compounds and metallocyclic oligomer compounds In this embodiment, the surface of the infrared absorbing nanoparticles according to this embodiment is coated with a coating film, which is a hydrolysis product in which all of the alkoxy groups, ether bonds, and ester bonds in the above-mentioned metal chelate compound or metal cyclic oligomer compound are hydrolyzed to form hydroxyl groups or carboxyl groups, a partial hydrolysis product in which a portion is hydrolyzed, and / or a polymer that has self-condensed through the hydrolysis reaction, to obtain the surface-treated infrared absorbing nanoparticles according to this embodiment. That is, the hydrolysis product in this embodiment is a concept that includes partial hydrolysis products.
[0042] However, in a reaction system in which an organic solvent such as alcohol is present, even if a sufficient amount of water is generally present in the system in terms of the stoichiometric composition, not all of the alkoxy groups, ether bonds, or ester bonds of the metal chelate compound or metal cyclic oligomer compound, which are the starting materials, are hydrolyzed depending on the type and concentration of the organic solvent. Therefore, depending on the conditions of the surface coating method described below, the compound may become amorphous after hydrolysis, with carbon C incorporated in the molecule. As a result, the coating film may contain undecomposed metal chelate compounds and / or cyclic metal oligomer compounds, but this is not a problem if the amount is small.
[0043] (4) Amount of surface treatment agent added The amount of the metal chelate compound or metal cyclic oligomer compound added is preferably 0.1 parts by mass or more and 1000 parts by mass or less in terms of metal element relative to 100 parts by mass of infrared absorbing nanoparticles. More preferably, it is in the range of 1 part by mass or more and 500 parts by mass or less. Even more preferably, it is in the range of 10 parts by mass or more and 150 parts by mass or less.
[0044] This is because, when the metal chelate compound or metal cyclic oligomer compound is 0.1 parts by mass or more, the hydrolysis products of these compounds or polymers of the hydrolysis products have the effect of coating the surface of the infrared absorbing microparticles, thereby improving the moist heat resistance. In addition, if the amount of the metal chelate compound or the metal cyclic oligomer compound is 1000 parts by mass or less, it is possible to avoid excessive adsorption onto the infrared absorbing fine particles. In addition, the improvement in moist heat resistance by the surface coating is not saturated, and an improvement in the coating effect can be expected.
[0045] Furthermore, by using 1000 parts by mass or less of the metal chelate compound or the cyclic metal oligomer compound, it is possible to avoid the problem of the particles being easily granulated by the hydrolysis product of the metal chelate compound or the cyclic metal oligomer compound or the polymer of the hydrolysis product when the medium is removed due to the excessive adsorption amount to the infrared absorbing particles. By avoiding the granulation of the particles, it is possible to ensure good transparency. In addition, an increase in production costs due to an increase in the amount of metal chelate compound or cyclic metal oligomer compound added and an increase in processing time caused by an excess of the metal chelate compound or cyclic metal oligomer compound can be avoided. Therefore, from an industrial viewpoint, it is preferable to set the amount of the metal chelate compound or cyclic metal oligomer compound added to 1000 parts by mass or less.
[0046] [3] Surface coating method for infrared absorbing particles In the surface coating method of infrared absorbing particles according to this embodiment, first, an infrared absorbing particle dispersion for forming a coating film (sometimes referred to as a "dispersion for forming a coating film" in this embodiment) is prepared by dispersing infrared absorbing particles in a suitable medium. Then, a surface treatment agent is added to the prepared dispersion for forming a coating film, and mixing and stirring are performed. Then, the surface of the infrared absorbing particles is coated with a coating film containing one or more selected from a hydrolysis product of a metal chelate compound, a polymer of a hydrolysis product of a metal chelate compound, a hydrolysis product of a metal cyclic oligomer compound, and a polymer of a hydrolysis product of a metal cyclic oligomer compound, and the surface-treated infrared absorbing particles according to this embodiment can be obtained. In the process of coating the surface of the infrared absorbing particles, the dispersion for forming a coating film to which the surface treatment agent has been added becomes a maturation liquid described later.
[0047] Here, the surface coating method of the infrared absorbing particles according to this embodiment will be described in the following order: (1) a surface coating method using a dispersion liquid for forming a coating film, (2) a surface coating method using a dispersion liquid for forming a coating film using water as a medium, (3) a surface coating method using a dispersion liquid for forming a coating film in which the amount of added water is adjusted, and (4) surface-treated infrared absorbing particles.
[0048] (1) Surface coating method using a dispersion for forming a coating film In the dispersion liquid for forming coating film according to the present embodiment, it is preferable to crush the composite tungsten oxide, which is infrared absorbing fine particles, finely in advance, disperse it in a suitable medium, and make it monodisperse.Then, it is essential to guarantee the dispersion state during this crushing and dispersion process, and not to aggregate the fine particles.This is to avoid the situation that the fine particles aggregate during the surface treatment process of infrared absorbing fine particles, the fine particles are surface-coated in the aggregate state, and the aggregate remains in the infrared absorbing fine particle dispersion described later, which reduces the transparency of the infrared absorbing fine particle dispersion and the infrared absorbing base material described later.
[0049] Therefore, by subjecting the dispersion for forming a coating film according to this embodiment to a pulverization / dispersion treatment, when the surface treatment agent according to this embodiment is added, the individual infrared absorbing nanoparticles can be uniformly and firmly coated with the hydrolysis product of the surface treatment agent and the polymer of the hydrolysis product.
[0050] Specific examples of the pulverization and dispersion treatment include pulverization and dispersion treatment methods using devices such as bead mills, ball mills, sand mills, paint shakers, ultrasonic homogenizers, etc. Among these, pulverization and dispersion treatments using media such as beads, balls, and Ottawa sand, using media agitation mills such as bead mills, ball mills, sand mills, and paint shakers, are preferred because they allow the desired dispersed particle size to be reached in a short time.
[0051] (2) Surface coating method using a dispersion liquid for forming a coating film using water as a medium The present inventors have found that in the surface coating method using the above-mentioned coating film-forming dispersion liquid, it is preferable to add the surface treatment agent according to this embodiment to the coating film-forming dispersion liquid containing water as a medium while stirring and mixing the infrared absorbing fine particles, and further to immediately complete the hydrolysis reaction of the added metal chelate compound and metal cyclic oligomer compound. In the present embodiment, the dispersion for forming a coating film may be referred to as "a dispersion for forming a coating film containing water as a medium."
[0052] This is believed to be due to the reaction order of the added surface treatment agent according to the present embodiment. That is, in a dispersion for forming a coating film using water as a medium, the hydrolysis reaction of the surface treatment agent always occurs first, and then the polymerization reaction of the generated hydrolysis product occurs. As a result, it is believed that the amount of carbon C remaining in the surface treatment agent molecule present in the coating film can be reduced compared to when water is not used as a medium. It is believed that a high-density coating film can be formed by reducing the amount of carbon C remaining in the surface treatment agent molecule present in the coating film.
[0053] In the above-mentioned dispersion for forming a coating film using water as a medium, the metal chelate compound, the metal cyclic oligomer compound, their hydrolysis products, and the polymers of the hydrolysis products may be decomposed to metal ions immediately after the start of addition. In that case, the decomposition to the metal ions ends when the aqueous solution becomes saturated.
[0054] On the other hand, in the dispersion liquid for forming a coating film using water as a medium, the dispersion concentration of the composite tungsten oxide in the dispersion liquid for forming a coating film is preferably 0.01 mass% or more and 80 mass% or less. If the dispersion concentration is in this range, the pH can be set to 8 or less, and the infrared absorbing nanoparticles according to this embodiment are kept dispersed by electrostatic repulsion.
[0055] As a result, the surfaces of all the infrared absorbing particles are covered with a coating film containing one or more selected from the hydrolysis products of metal chelate compounds, polymerized products of hydrolysis products of metal chelate compounds, hydrolysis products of metal cyclic oligomer compounds, and polymerized products of hydrolysis products of metal cyclic oligomer compounds, and it is considered that the surface-treated infrared absorbing particles according to this embodiment are produced. The coating film forming dispersion liquid to which the surface treatment agent has been added becomes a matured liquid, and a coating film is formed on the surfaces of the infrared absorbing particles.
[0056] The thickness of the coating film of the surface-treated infrared absorbing particles according to this embodiment is preferably 0.5 nm or more. This is because if the coating film has a thickness of 0.5 nm or more, the surface-treated infrared absorbing particles are considered to exhibit sufficient moist heat resistance and chemical stability. On the other hand, from the viewpoint of ensuring that the surface-treated infrared absorbing particles have predetermined optical properties, it is considered preferable that the coating film has a thickness of 100 nm or less. In addition, the thickness is preferably 0.5 nm or more and 20 nm or less, and more preferably 1 nm or more and 10 nm or less. The thickness of the coating film can be measured using a transmission electron microscope, and the area where there are no lattice fringes (arrangement of atoms in a crystal) of the surface-treated infrared absorbing particles corresponds to the coating film.
[0057] (3) Surface coating method using a dispersion for forming a coating film with an adjusted amount of added water As a variation of the above-mentioned method for preparing the coating film-forming dispersion liquid using water as a medium, there is also a method in which an organic solvent is used as the medium of the coating film-forming dispersion liquid, and the above-mentioned reaction sequence is realized while adjusting the amount of added water to an appropriate value. In this embodiment, the coating film-forming dispersion liquid may be referred to as "a coating film-forming dispersion liquid using an organic solvent as a medium." This preparation method is also convenient when it is desired to reduce the amount of water contained in the coating film-forming dispersion for convenience of the subsequent steps.
[0058] Specifically, the surface treatment agent according to the present embodiment and pure water are dropped in parallel while stirring and mixing the dispersion liquid for forming the coating film, which is made of an organic solvent as a medium, and the infrared absorbing fine particles. At this time, the medium temperature, which affects the reaction rate, and the dropping speed of the surface treatment agent and the pure water are appropriately controlled. Note that the organic solvent may be any solvent that dissolves in water at room temperature, such as an alcohol-based, ketone-based, or glycol-based solvent, and various types can be selected.
[0059] (4) Surface-treated infrared absorbing particles The surface-treated infrared-absorbing nanoparticles according to this embodiment obtained by the surface coating method using the above-mentioned dispersion liquid for forming a coating film can be used as a raw material for an infrared-absorbing nanoparticle dispersion or an infrared-absorbing base material in the form of nanoparticles or dispersed in a liquid medium or a solid medium. In other words, the resulting surface-treated infrared absorbing fine particles do not require further heat treatment to increase the density or chemical stability of the coating film, because the heat resistance is imparted by the addition of the silicon compound described below.
[0060] However, it is possible to heat-treat the coating film-forming dispersion (matured liquid) to which a surface treatment agent has been added or the surface-treated infrared-absorbing microparticle powder for the purpose of obtaining a powder of surface-treated infrared-absorbing microparticles from the coating film-forming dispersion, drying the obtained surface-treated infrared-absorbing microparticle powder, etc. In this case, however, care must be taken so that the heat treatment temperature does not exceed the temperature at which the surface-treated infrared-absorbing microparticles strongly aggregate to form strong aggregates.
[0061] This is because the surface-treated infrared-absorbing particles according to this embodiment are often required to have transparency in the infrared-absorbing particle dispersion or infrared-absorbing substrate that is finally used, due to their intended use. If an infrared-absorbing particle dispersion or an infrared-absorbing substrate is produced using an aggregate as an infrared-absorbing material, a high degree of cloudiness (haze) will be obtained. If the heat treatment is performed at a temperature exceeding the temperature at which strong aggregates are formed, the strong aggregates will be crushed and redispersed in a dry or / and wet manner in order to ensure the transparency of the infrared-absorbing particle dispersion or the infrared-absorbing substrate. However, when the surface-treated infrared-absorbing particles are crushed and redispersed, the coating film on the surface of the surface-treated infrared-absorbing particles may be damaged, and in some cases, part of the coating film may peel off, exposing the surface of the particles.
[0062] As described above, the surface-treated infrared absorbing particles according to this embodiment do not require a heat treatment after the mixing and stirring process, so they do not cause strong aggregation, and therefore a dispersion process for breaking down strong aggregation is not required or can be performed in a short time. As a result, the coating film of the surface-treated infrared absorbing particles according to this embodiment is not damaged and remains coating each individual infrared absorbing particle.
[0063] As described above, a high-density coating film can be formed by reducing the amount of carbon C remaining in the molecules of the surface treatment agent present in the coating film. From this viewpoint, the carbon concentration in the surface-treated infrared absorbing microparticle powder made of the surface-treated infrared absorbing microparticles is preferably 0.2% by mass or more and 5.0% by mass or less. More preferably, it is 0.5% by mass or more and 3.0% by mass or less.
[0064] [4] Silicon compound addition and infrared absorbing composite particles By adding a silicon compound to the surface-treated infrared absorbing nanoparticles according to this embodiment, it is possible to obtain the infrared absorbing composite nanoparticles according to this embodiment. The silicon compound to be added to the surface-treated infrared absorbing fine particles is not particularly limited, but a preferred example is silica fine particles. The silica fine particles preferably have an average particle size of 10 nm to 50 nm. Such silica fine particles may be commercially available silica fine particles or silica fine particles obtained by hydrolysis of an organosilicon compound. If the average particle size of the silica fine particles is 50 nm or less, it is preferable because it does not adversely affect optical properties such as worsening the haze of the infrared absorbing fine particle dispersion described below.
[0065] The surface-treated infrared-absorbing particles become infrared-absorbing composite particles when silicon compound particles such as silica particles are present in one or more locations selected from within the coating film of the surface-treated infrared-absorbing particles, on the coating film, and near the surface. The silicon compound particles such as silica particles are present in one or more locations selected from within the coating film of the infrared-absorbing composite particles, on the coating film, and near the surface, thereby strengthening the coating film of the infrared-absorbing composite particles and improving heat resistance.
[0066] [5] Method of adding silicon compounds The silicon compound can be added in the process of adding a surface treatment agent to the coating film-forming dispersion, that is, in the process of synthesizing the surface-treated infrared absorbing particles, in the process of adding the silicon compound before the solvent is removed by drying after the surface-treated infrared absorbing particles are synthesized in the coating film-forming dispersion (aged liquid) to which the surface treatment agent has been added, and in the process of preparing the infrared absorbing particle dispersion described below. The amount of the silicon compound added is preferably 1% by mass or more and 30% by mass or less relative to the infrared absorbing particles. More preferably, it is 1% by mass or more and 20% by mass. If the amount of the silicon compound added to the surface-treated infrared absorbing particles is 1% by mass or more, the heat resistance is exhibited. If it is 30% by mass or less, there is no adverse effect on the optical properties, such as the haze of the infrared absorbing particle dispersion being deteriorated. The content of the silicon compound can be calculated from the quantitative results of silicon by ICP (inductively coupled plasma) analysis.
[0067] In order to add a silicon compound in the process of synthesizing the surface-treated infrared absorbing fine particles, a surface treatment agent and a silicon compound are added simultaneously using a dispersion liquid for forming a coating film (ripened liquid). As a result, a coating film is formed, and infrared absorbing composite fine particles having the silicon compound incorporated in the coating film can be obtained.
[0068] There is a method in which surface-treated infrared absorbing microparticles are obtained using a coating film-forming dispersion liquid (aged liquid) to which a surface treatment agent has been added, and then a silicon compound is added and the solvent is removed by drying to obtain infrared absorbing composite microparticles having a silicon compound present near the surface of the infrared absorbing composite microparticles. Furthermore, even if a silicon compound is added to an infrared absorbing microparticle dispersion liquid containing surface-treated infrared absorbing microparticles, it is possible to obtain infrared absorbing composite microparticles in which the silicon compound is present near the surface of the infrared absorbing composite microparticles in the infrared absorbing microparticle dispersion described below.
[0069] In the present invention, the vicinity of the surface of the infrared absorbing composite particles means a distance of 10 nm or less from the surface of the infrared absorbing composite particles. If the distance between the silicon compound and the infrared absorbing composite particles is 10 nm or less, it is considered that the effect of heat resistance is exhibited.
[0070] Among these methods of adding silicon compound, the method of adding in the process of synthesizing surface-treated infrared absorbing microparticles, or the method of adding in the surface-treated infrared absorbing microparticles that are surface-coated with the dispersion liquid for forming a coating film (ripening liquid) to which a surface treatment agent is added, before the solvent is removed by drying, is preferred. In either case, a silicon compound dispersion liquid in which the silicon compound is dispersed in a solvent is prepared, and the silicon compound is added to each dispersion liquid. This is because the silicon compound can be present in one or more locations selected from the inside, the on, and the surface vicinity of the coating film of the infrared absorbing composite microparticles. When adding a silicon compound, it is preferable to prepare a silicon compound dispersion liquid dispersed in a solvent. The method of adding the silicon compound dispersion liquid is selected according to the dispersion medium of the dispersion liquid to which the silicon compound is added. For example, when adding to a surface treatment agent, a silicon compound dispersion liquid that matches the solvent of the surface treatment agent is selected. When adding to a surface treatment infrared absorbing nanoparticle dispersion liquid, a silicon compound that is dispersed in the same dispersion medium or a solvent that does not impair dispersibility is selected.
[0071] In addition, to obtain a silicon compound dispersion, a collision type high-pressure emulsifier (ultra-high-pressure homogenizer) that applies high pressure to cause fine particles moving at high speed in a solvent to collide with each other, or a high-pressure homogenizer that utilizes the turbulence effect when passing through a nozzle, etc. Also, a commercially available silicon compound dispersion may be used.
[0072] [6] Infrared-absorbing nanoparticle dispersion, infrared-absorbing nanoparticle dispersion, infrared-absorbing substrate, and article obtained using infrared-absorbing composite nanoparticles Hereinafter, the infrared absorbing microparticle dispersion, infrared absorbing microparticle dispersion, and infrared absorbing substrate obtained using the infrared absorbing composite microparticles according to this embodiment, as well as articles using them, will be described in the following order: (1) infrared absorbing microparticle dispersion, (2) infrared absorbing microparticle dispersion, (3) infrared absorbing substrate, and (4) articles using the infrared absorbing microparticle dispersion or infrared absorbing substrate.
[0073] (1) Infrared absorbing nanoparticle dispersion The infrared absorbing nanoparticle dispersion according to this embodiment is a dispersion of the infrared absorbing composite nanoparticles according to this embodiment in a liquid medium, which may be one or more liquid media selected from organic solvents, oils and fats, liquid plasticizers, compounds that are polymerized by curing, and water. The infrared absorbing microparticle dispersion liquid according to this embodiment will be described in the following order: (i) production method, (ii) organic solvent used, (iii) oils and fats used, (iv) liquid plasticizer used, (v) compound that is polymerized by curing used, (vi) dispersant used, and (vii) method of using the infrared absorbing microparticle dispersion liquid.
[0074] (i) Manufacturing method To produce the infrared absorbing microparticle dispersion according to this embodiment, the above-mentioned surface treatment and silicon compound addition coating film forming dispersion is heated or dried under conditions that can avoid strong aggregation of infrared absorbing composite microparticles, or dried by vacuum fluidized drying, spray drying, etc. at room temperature, to obtain the infrared absorbing composite microparticle powder according to this embodiment. Then, the infrared absorbing composite microparticle powder is added to the above-mentioned liquid medium to be redispersed. In addition, it is also preferable to separate the surface treatment and silicon compound addition coating film forming dispersion into infrared absorbing composite microparticles and medium, and replace the medium of the coating film forming dispersion with the medium of the infrared absorbing microparticle dispersion (so-called solvent replacement) to produce the infrared absorbing microparticle dispersion.
[0075] In the treatment by vacuum fluidized drying, the drying and disintegration treatments are performed simultaneously under a reduced pressure atmosphere, so that the drying speed is fast and aggregation of the infrared-absorbing composite microparticles can be avoided. In addition, since the drying is performed under a reduced pressure atmosphere, the volatile components can be removed even at a relatively low temperature, and the amount of the remaining volatile components can be reduced to an extremely small amount. In addition, in the treatment by spray drying, secondary aggregation due to the surface force of the volatile components is unlikely to occur, and an infrared-absorbing composite microparticle powder containing infrared-absorbing composite microparticles that are relatively free of secondary aggregation can be obtained without disintegration treatment. In the infrared absorbing composite microparticles contained in the infrared absorbing composite microparticle powder, the carbon concentration is preferably 0.2% by mass or more and 5.0% by mass or less, more preferably 0.5% by mass or more and 3.0% by mass or less, similar to the above-mentioned surface-treated infrared absorbing microparticle powder.
[0076] On the other hand, it is also a preferred configuration to previously match the medium of the dispersion liquid for forming a coating film with the medium of the dispersion liquid for forming infrared absorbing microparticles, and to use the dispersion liquid for forming a coating film after the surface treatment and the addition of the silicon compound as the dispersion liquid for infrared absorbing microparticles as it is.
[0077] (ii) Organic solvent used As the organic solvent used in the infrared absorbing nanoparticle dispersion liquid according to this embodiment, an alcohol-based, ketone-based, hydrocarbon-based, glycol-based, water-based, or the like can be used. Specifically, alcohol-based solvents such as methanol, ethanol, 1-propanol, isopropanol, butanol, pentanol, benzyl alcohol, and diacetone alcohol; Ketone solvents such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, cyclohexanone, and isophorone; Ester solvents such as 3-methyl-methoxy-propionate; Glycol derivatives such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol isopropyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, and propylene glycol ethyl ether acetate; Amides such as formamide, N-methylformamide, dimethylformamide, dimethylacetamide, and N-methyl-2-pyrrolidone; Aromatic hydrocarbons such as toluene and xylene; Ethylene chloride, chlorobenzene, and the like can be used. Among these organic solvents, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether acetate, n-butyl acetate, and the like can be preferably used.
[0078] (iii) Fats and oils used The oil used in the infrared absorbing nanoparticle dispersion liquid according to this embodiment is preferably a vegetable oil or a vegetable-derived oil. Examples of vegetable oils that can be used include drying oils such as linseed oil, sunflower oil, tung oil, and perilla oil; semi-drying oils such as sesame oil, cottonseed oil, rapeseed oil, soybean oil, rice bran oil, and poppy oil; and non-drying oils such as olive oil, coconut oil, palm oil, and dehydrated castor oil. As the compound derived from vegetable oil, fatty acid monoesters and ethers obtained by directly esterifying fatty acids of vegetable oil with monoalcohols can be used. Commercially available petroleum-based solvents can also be used as the oils and fats. Commercially available petroleum-based solvents that can be used include Isopar (registered trademark) E, Exxor (registered trademark) Hexane, Heptane, E, D30, D40, D60, D80, D95, D110, and D130 (all manufactured by ExxonMobil).
[0079] (iv) Liquid plasticizer used As the liquid plasticizer used in the infrared absorbing nanoparticle dispersion liquid according to the present embodiment, for example, a plasticizer which is a compound of a monohydric alcohol and an organic acid ester, an ester-based plasticizer such as a polyhydric alcohol organic acid ester compound, a phosphoric acid-based plasticizer such as an organic phosphoric acid-based plasticizer, etc. can be used. Note that it is preferable that any of them is liquid at room temperature. Among them, the plasticizer that is an ester compound synthesized from polyhydric alcohol and fatty acid can be preferably used.The ester compound synthesized from the polyhydric alcohol and fatty acid is not particularly limited, but for example, glycol-based ester compounds obtained by reacting glycol such as triethylene glycol, tetraethylene glycol, tripropylene glycol with monobasic organic acid such as butyric acid, isobutyric acid, caproic acid, 2-ethylbutyric acid, heptyl acid, n-octylic acid, 2-ethylhexyl acid, pelargonic acid (n-nonylic acid), decyl acid, etc. can be used. Further examples include ester compounds of tetraethylene glycol or tripropylene glycol with the above-mentioned monobasic organic compounds. Among them, fatty acid esters of triethylene glycol such as triethylene glycol dihexanate, triethylene glycol di-2-ethylbutyrate, triethylene glycol di-octanate, triethylene glycol di-2-ethylhexanoate, etc. can be used. Furthermore, fatty acid esters of triethylene glycol can also be preferably used.
[0080] (v) Compounds used that become polymerized by curing The compound that is polymerized by curing and is used in the infrared absorbing nanoparticle dispersion liquid according to this embodiment is a monomer or oligomer that forms a polymer by polymerization or the like. Specifically, methyl methacrylate monomer, acrylate monomer, styrene resin monomer, etc. can be used.
[0081] The liquid mediums described above can be used in combination of two or more kinds. Furthermore, if necessary, an acid or an alkali may be added to these liquid media to adjust the pH.
[0082] (vi) Dispersant used In the infrared absorbing nanoparticle dispersion liquid according to this embodiment, in order to further improve the dispersion stability of the infrared absorbing composite nanoparticles and to prevent the dispersed particles from becoming coarse due to re-aggregation, it is also preferable to add various dispersants, surfactants, coupling agents, and the like. The dispersant, coupling agent, and surfactant can be selected according to the application, but it is preferable that they have an amine-containing group, a hydroxyl group, a carboxyl group, a sulfo group, or an epoxy group as a functional group. These functional groups adsorb to the surface of the infrared absorbing composite particles to prevent aggregation and disperse them uniformly. Polymer dispersants having any of these functional groups in the molecule are more preferable.
[0083] In addition, acrylic-styrene copolymer-based dispersants having functional groups are also preferred. Among them, acrylic-styrene copolymer-based dispersants having a carboxyl group as a functional group and acrylic-based dispersants having an amine-containing group as a functional group are more preferred. Dispersants having an amine-containing group as a functional group preferably have a molecular weight Mw of 2000 to 200000 and an amine value of 5 to 100 mgKOH / g. In addition, dispersants having a carboxyl group preferably have a molecular weight Mw of 2000 to 200000 and an acid value of 1 to 50 mgKOH / g.
[0084] Specific examples of commercially available dispersants include SOLSPERSE (registered trademark) 3000, 5000, 9000, 11200, 12000, 13000, 13240, 13650, 13940, 16000, 17000, 18000, 20000, 21000, 24000SC, 24000GR, 26000, 27000, and 280 manufactured by Lubrizol Japan. 00, 31845, 32000, 32500, 32550, 32600, 33000, 33500, 34750, 35100, 35200, 36600, 37500, 38500, 39000, 41000, 41090, 53095, 55000, 56000, 71000, 76500, J180, J200, M387, etc.; SOLPLUS (registered trademark) (hereinafter the same) D5 10, D520, D530, D540, DP310, K500, L300, L400, R700, etc.; Disperbyk (registered trademark) manufactured by BYK Japan (hereinafter the same) -101, 102, 103, 106, 107, 108, 109, 110, 111, 112, 116, 130, 140, 142, 145, 154, 161, 162, 163, 164, 165, 16 6, 167, 168, 170, 171, 174, 180, 181, 182, 183, 184, 185, 190, 191, 192, 2000, 2001, 2009, 2020, 2025, 2050, 2070, 2095, 2096, 2150, 2151, 2152, 2155, 2163, 2164, Anti-Terra (registered trademark) (hereinafter the same)-U, 203, 204, etc.;BYK (registered trademark) (hereinafter the same)-P104, P104S, P105, P9050, P9051, P9060, P9065, P9080, 051, 052, 053, 054, 055, 057, 063, 065, 066N, 067A, 077, 088, 141, 220S, 300, 302, 306, 307, 310, 315, 320, 322, 323, 325, 330, 331, 333, 337, 340, 345, 346, 347, 348, 350, 354, 355, 358N, 361N, 370, 375, 377, 378, 380N, 381, 392, 410, 425, 430, 1752, 4510, 6919, 9076, 9077, W909, W935, W940, W961, W966, W969, W972, W980, W985, W995, W996, W9010, Dynwet80 0, Cyclean3700, UV3500, UV3510, UV3570, etc.; EFKA (registered trademark) manufactured by EFKA Additives (hereinafter the same) 2020, 2025, 3030, 3031, 3236, 4008, 4009, 4010, 4015, 4020, 4046, 4047, 4050, 4055, 4060, 4080, 4300, 4310, 4320, 4330, 4340, 4400, 440 1, 4402, 4403, 4500, 5066, 5220, 6220, 6225, 6230, 6700, 6780, 6782, 7462, 8503, etc.; JONCRYL (registered trademark) manufactured by BASF Japan Ltd. (hereinafter the same) 67, 678, 586, 611, 680, 682, 690, 819, -JDX5050, etc.; TERPLUS (registered trademark) manufactured by Otsuka Chemical Co., Ltd. (hereinafter the same) MD1000, D1180, D 1130, etc.; Ajisper (registered trademark) (hereinafter the same) PB-711, PB-821, PB-822, etc., manufactured by Ajinomoto Fine-Techno Co., Ltd.; Disparlon (registered trademark) (hereinafter the same) 1751N, 1831, 1850, 1860, 1934, DA-400N, DA-703-50, DA-325, DA-375, DA-550, DA-705, DA-725, DA-1401, DA-7301, DN-900, NS-5210, NVI-8514L, etc., manufactured by Kusumoto Chemicals Co., Ltd.Examples of such products include Arphon (registered trademark) (hereinafter the same) UH-2170, UC-3000, UC-3910, UC-3920, UF-5022, UG-4010, UG-4035, UG-4040, and UG-4070, and Reseda (registered trademark) (hereinafter the same) GS-1015, GP-301, and GP-301S, manufactured by Toagosei Co., Ltd.; and Dianale (registered trademark) (hereinafter the same) BR-50, BR-52, BR-60, BR-73, BR-77, BR80, BR-83, BR85, BR87, BR88, BR-90, BR-96, BR102, BR-113, and BR116, manufactured by Mitsubishi Chemical Corporation.
[0085] (vii) Method for using the infrared absorbing nanoparticle dispersion The infrared absorbing nanoparticle dispersion liquid according to the present embodiment produced as described above can be applied to the surface of a suitable substrate to form a dispersion film thereon, and used as an infrared absorbing substrate to be described later. In other words, the dispersion film is a kind of dried solidified product of the infrared absorbing nanoparticle dispersion liquid. Moreover, the infrared absorbing microparticle dispersion liquid can be dried and pulverized to obtain a powdered infrared absorbing microparticle dispersion according to the present embodiment (sometimes referred to as "dispersed powder" in the present embodiment). In other words, the dispersed powder is a type of dried solidified product of the infrared absorbing microparticle dispersion liquid. The dispersed powder is a powdered dispersion in which infrared absorbing composite microparticles are dispersed in a solid medium (such as a dispersant), and is distinguished from the infrared absorbing composite microparticle powder described above. Since the dispersed powder contains a dispersant, it is possible to easily redisperse the infrared absorbing composite microparticles in a medium by mixing with an appropriate medium.
[0086] The dispersed powder can be used as a raw material for adding the infrared absorbing composite fine particles in a dispersed state to an infrared absorbing product. That is, the dispersed powder in which the infrared absorbing composite fine particles according to the present embodiment are dispersed in a solid medium may be dispersed again in a liquid medium and used as a dispersion liquid for an infrared absorbing product, or the dispersed powder may be kneaded into a resin as described later.
[0087] On the other hand, an infrared absorbing nanoparticle dispersion liquid in which the infrared absorbing composite nanoparticles according to this embodiment are mixed and dispersed in a liquid medium can be used for various applications utilizing light-to-heat conversion. For example, the infrared absorbing composite particles can be added to an uncured thermosetting resin, or the infrared absorbing composite particles according to this embodiment are dispersed in an appropriate solvent, and then an uncured thermosetting resin is added to obtain a curable ink composition. The curable ink composition is provided on a predetermined substrate, and when it is cured by being irradiated with infrared rays, etc., it has excellent adhesion to the substrate. In addition to being used as a conventional ink, the curable ink composition can be applied in a predetermined amount, irradiated with infrared rays or other electromagnetic waves, cured, and stacked up to become an optimal curable ink composition for a stereolithography method for forming a three-dimensional object.
[0088] (2) Infrared absorbing nanoparticle dispersion The infrared absorbing nanoparticle dispersion according to this embodiment is a dispersion in which the infrared absorbing composite nanoparticles according to this embodiment are dispersed in a solid medium. The solid medium may be a resin, glass, or other solid medium. The infrared absorbing nanoparticle dispersion according to this embodiment will be described in the order of (i) the production method and (ii) heat resistance.
[0089] (i) Manufacturing method When the infrared absorbing composite particles according to the present embodiment are kneaded into resin and molded into a film or board, the infrared absorbing composite particles can be kneaded directly into the resin. It is also possible to mix the infrared absorbing particle dispersion liquid with the resin, or to add a powder dispersion in which the infrared absorbing composite particles are dispersed in a solid medium to a liquid medium and then mix it with the resin. When a resin is used as the solid medium, it may be in the form of a film or board having a thickness of, for example, 0.1 μm to 50 mm.
[0090] Generally, when the infrared absorbing composite particles according to this embodiment are kneaded into a resin, they are mixed and kneaded while being heated at a temperature near the melting point of the resin (approximately 200 to 300° C.). In this case, the infrared absorbing composite particles can be further mixed with a resin and pelletized, and the pellets can be formed into a film or board by various methods. For example, they can be formed by extrusion molding, inflation molding, solution casting, casting, etc. The thickness of the film or board can be appropriately set depending on the purpose of use, and the amount of filler relative to the resin (i.e., the amount of the infrared absorbing composite particles according to this embodiment) can be varied depending on the thickness of the substrate and the required optical and mechanical properties, but is generally preferably 50 mass % or less relative to the resin. When the amount of the filler relative to the resin is 50% by mass or less, the particles in the solid resin can be prevented from granulating with each other, so that good transparency can be maintained. In addition, the amount of the infrared absorbing composite particles according to this embodiment can be controlled, which is advantageous in terms of cost.
[0091] On the other hand, the infrared absorbing microparticle dispersion in which the infrared absorbing composite microparticles according to the present embodiment are dispersed in a solid medium can also be used in a state of being further pulverized into powder.When adopting this configuration, the infrared absorbing composite microparticles according to the present embodiment are already sufficiently dispersed in the solid medium in the powdered infrared absorbing microparticle dispersion.Therefore, the powdered infrared absorbing microparticle dispersion can be dissolved in a suitable liquid medium as a so-called master batch, or kneaded with resin pellets, etc., to easily produce a liquid or solid infrared absorbing microparticle dispersion.
[0092] The resin that becomes the matrix of the above-mentioned film or board is not particularly limited and can be selected according to the application. As a resin that is low cost, highly transparent, and versatile, PET resin, acrylic resin, polyamide resin, vinyl chloride resin, polycarbonate resin, olefin resin, epoxy resin, polyimide resin, etc. can be used. In addition, fluororesin can also be used in consideration of weather resistance.
[0093] (ii) Heat resistance The infrared absorbing nanoparticle dispersion of this embodiment has excellent heat resistance, and when the dispersion is set to have a total light transmittance of approximately 85%, and is exposed to a high-temperature atmosphere at 120°C for 125 hours, the rate of change in visible light transmittance before and after the exposure is 1% or less, the rate of change in solar radiation transmittance is 3.5% or less, and more preferably the rate of change in solar radiation transmittance can be made 3% or less.
[0094] (3) Infrared absorbing substrate The infrared absorbing substrate according to this embodiment has a dispersion film containing the infrared absorbing composite fine particles according to this embodiment formed on the surface of a given substrate. Since a dispersion film containing the infrared absorbing composite fine particles according to this embodiment is formed on the surface of a specific substrate, the infrared absorbing substrate according to this embodiment has excellent heat resistance and chemical stability, and can be suitably used as an infrared absorbing material. The infrared absorbing substrate according to this embodiment will be described in the order of (i) the production method and (ii) heat resistance.
[0095] (i) Manufacturing method For example, the infrared absorbing composite particles according to the present embodiment are mixed with a liquid medium such as an organic solvent such as alcohol or water, a resin binder, and optionally a dispersant to obtain an infrared absorbing particle dispersion. The obtained infrared absorbing particle dispersion is applied to a suitable substrate surface, and then the liquid medium is removed or cured to obtain an infrared absorbing substrate in which the infrared absorbing particle dispersion is directly laminated on the substrate surface.
[0096] The resin binder component can be selected according to the application, and examples of the resin binder component include an ultraviolet curing resin, a heat curing resin, a room temperature curing resin, a thermoplastic resin, etc. On the other hand, an infrared absorbing nanoparticle dispersion liquid not containing a resin binder component may be laminated on the surface of a substrate with an infrared absorbing nanoparticle dispersion, or after the lamination, a liquid medium containing a binder component may be applied onto the layer of the infrared absorbing nanoparticle dispersion.
[0097] Specifically, an infrared absorbing substrate is prepared by applying a liquid infrared absorbing microparticle dispersion in which infrared absorbing composite microparticles are dispersed in one or more liquid media selected from organic solvents, organic solvents in which resins are dissolved, organic solvents in which resins are dispersed, and water to the surface of the substrate, and solidifying the resulting coating film by an appropriate method. In addition, an infrared absorbing substrate is prepared by applying a liquid infrared absorbing microparticle dispersion containing a resin binder component to the surface of the substrate, and solidifying the resulting coating film by an appropriate method. In addition, an infrared absorbing substrate is prepared by applying a liquid infrared absorbing microparticle dispersion in which infrared absorbing composite microparticles are dispersed in a powdery solid medium to a predetermined medium, to the surface of the substrate, and solidifying the resulting coating film by an appropriate method. Of course, an infrared absorbing substrate is prepared by applying an infrared absorbing microparticle dispersion in which two or more of the various liquid infrared absorbing microparticle dispersions are mixed to the surface of the substrate, and solidifying the resulting coating film by an appropriate method.
[0098] The material of the above-mentioned substrate is not particularly limited as long as it is transparent, but glass, a resin board, a resin sheet, or a resin film is preferably used. Resins used for resin boards, resin sheets, and resin films are not particularly limited as long as they do not cause problems in the surface state or durability of the required boards, sheets, and films. For example, boards, sheets, and films made of transparent polymers such as polyester polymers such as polyethylene terephthalate and polyethylene naphthalate, cellulose polymers such as diacetyl cellulose and triacetyl cellulose, polycarbonate polymers, acrylic polymers such as polymethyl methacrylate, styrene polymers such as polystyrene and acrylonitrile-styrene copolymers, polyethylene, polypropylene, polyolefins having a cyclic or norbornene structure, olefin polymers such as ethylene-propylene copolymers, vinyl chloride polymers, amide polymers such as aromatic polyamides, imide polymers, sulfone polymers, polyethersulfone polymers, polyetheretherketone polymers, polyphenylene sulfide polymers, vinyl alcohol polymers, vinylidene chloride polymers, vinyl butyral polymers, arylate polymers, polyoxymethylene polymers, epoxy polymers, and further various binary and ternary copolymers, graft copolymers, and blends thereof can be mentioned. In particular, polyester-based biaxially oriented films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate are preferred in terms of mechanical properties, optical properties, heat resistance, and economic efficiency. The polyester-based biaxially oriented film may be a copolymer polyester-based film.
[0099] (ii) Heat resistance In the above infrared absorbing base material, when the infrared absorbing base material with a total visible light transmittance set to 85% is exposed to a high-temperature atmosphere at 120°C for 125 hours, the rate of change in visible light transmittance before and after the exposure is 1% or less, the rate of change in solar radiation transmittance is 3.5% or less, and more preferably the rate of change in solar radiation transmittance can be made 3% or less, and the base material has excellent heat resistance.
[0100] (4) Articles using infrared absorbing nanoparticle dispersions or infrared absorbing substrates As described above, the infrared absorbing nanoparticle dispersion and the infrared absorbing substrate according to the present embodiment are excellent in heat resistance and chemical stability. As a result, various infrared absorbing articles manufactured using the infrared absorbing nanoparticle dispersion and the infrared absorbing substrate are also excellent in heat resistance and chemical stability. Therefore, these infrared absorbing articles can be suitably used, for example, in window materials in various buildings and vehicles, intended to block light in the infrared region while allowing sufficient visible light in, thereby suppressing an increase in temperature inside the room while maintaining brightness. EXAMPLES
[0101] The present embodiment will be specifically described below with reference to examples, but the present embodiment is not limited to the following examples. The particle size of the fine particles dispersed in the dispersion in the examples and comparative examples is shown as an average value measured by a particle size measuring device based on dynamic light scattering (ELS-8000 manufactured by Otsuka Electronics Co., Ltd.). The crystallite size was measured by powder X-ray diffraction method (θ-2θ method) using a powder X-ray diffractometer (X'Pert-PRO / MPD manufactured by PANalytical, Spectris Co., Ltd.), and calculated by the Rietveld method. The thickness of the coating film of the infrared-absorbing composite particles and the state of the presence of silica particles were determined by reading the areas of the infrared-absorbing particles without lattice fringes as coating films from 300,000x magnification photographic data obtained using a transmission electron microscope (HF-2200, Hitachi, Ltd.). The silica content in the surface-treated infrared absorbing fine particle dispersion powder was determined by quantifying silicon using ICP emission spectrometry. The visible light transmittance (VLT) and solar transmittance (ST21) were measured in accordance with ISO 9050 and JIS R 3106. Specifically, the transmittance was measured using a spectrophotometer U-4100 manufactured by Hitachi High-Tech Corporation, and calculated by multiplying it by a coefficient according to the spectrum of sunlight. The heat resistance of the infrared absorbing sheet was evaluated by exposing the sheet, which has a visible light transmittance of about 85%, to a high-temperature atmosphere at 120°C for 125 hours. If the rate of change in solar radiation transmittance was within 3.5%, it was determined that there was no problem. The optical characteristic values of the infrared absorbing sheet referred to here include the optical characteristic values of the resin sheet that is the base material.
[0102] [Example 1] The infrared absorbing particles were prepared using hexagonal cesium tungsten bronze (Cs) with a Cs / W (molar ratio) of 0.33. 0.33 A mixture of 28% by mass of WO3 powder (YM-01 manufactured by Sumitomo Metal Mining Co., Ltd.) and 72% by mass of pure water was loaded into a paint shaker containing 0.3 mmφ ZrO2 beads and ground and dispersed for 10 hours to obtain the Cs according to Example 1. 0.33 WO z A dispersion of fine particles was obtained. 0.33 The dispersed particle diameter of the WO3 microparticles was measured to be 100 nm. The particle refractive index was set to 1.81 and the particle shape was non-spherical as the particle diameter measurement settings. The background was measured using pure water, and the solvent refractive index was set to 1.33. After removing the solvent from the obtained dispersion, the crystallite diameter was measured to be 32 nm. The obtained Cs 0.33 The dispersion of WO3 particles was mixed with pure water, and Cs 0.33 A coating film-forming dispersion A according to Example 1 was obtained, in which the concentration of WO3 fine particles was 14 mass %. On the other hand, 29.0% by mass of aluminum ethyl acetoacetate diisopropylate as an aluminum-based chelate compound and 71.0% by mass of isopropyl alcohol (IPA) were mixed to obtain a diluted surface treatment agent a.
[0103] 2000g of the obtained dispersion A for forming a coating film was placed in a beaker, and 1000g of the diluted solution a of the surface treatment agent was added dropwise thereto over 5 hours while stirring. After the dropwise addition of the diluted solution a of the surface treatment agent, stirring was further performed at a temperature of 20°C for 24 hours to prepare an aged liquid according to Example 1. Surface-treated infrared absorbing fine particles were formed in the aged liquid. Next, 112g of a 20% by mass silica fine particle aqueous dispersion was added to 650g of the aged liquid, and the medium was evaporated from the aged liquid by vacuum flow drying to obtain a powder containing infrared absorbing composite fine particles according to Example 1 (infrared absorbing composite fine particle powder). The infrared absorbing composite fine particles according to Example 1 were observed by TEM to read the state of the coating film, and it was confirmed that a coating film covering the lattice stripes and silica fine particles were present in the vicinity of the coating film. The silica aqueous dispersion was obtained by dispersing silica fine particles having an average particle diameter of 20nm and water as a solvent using a collision type high-pressure emulsifier.
[0104] 8% by mass of the infrared absorbing composite microparticles according to Example 1, 24% by mass of a polyacrylate-based dispersant, and 68% by mass of toluene were mixed. The resulting mixture was loaded into a paint shaker containing 0.3 mmφZrO2 beads, and ground and dispersed for 1 hour to obtain an infrared absorbing microparticle dispersion according to Example 1. Next, the medium was evaporated from this infrared absorbing microparticle dispersion by vacuum fluidized drying, to obtain an infrared absorbing microparticle dispersion powder according to Example 1. The content of silica microparticles in the infrared absorbing microparticle dispersion powder was 4.8% by mass.
[0105] The infrared absorbing microparticle dispersion powder according to Example 1 and a polycarbonate resin were dry-blended so that the total light transmittance of the infrared absorbing sheet obtained later would be about 85%. The resulting blend was kneaded at 290°C using a twin-screw extruder, extruded from a T-die, and formed into a sheet material with a thickness of 0.75 mm by a calendar roll method, thereby obtaining the infrared absorbing sheet according to Example 1. The infrared absorbing sheet is an example of the infrared absorbing microparticle dispersion according to this embodiment.
[0106] The optical properties of the obtained infrared absorbing sheet according to Example 1 were measured, and the initial visible transmittance and solar transmittance of the sheet used for the atmosphere exposure were 85.40% and 67.6%, respectively. After exposure to a high-temperature atmosphere, the visible transmittance and solar transmittance were 85.47% and 68.59%, respectively, and the change rate of the visible transmittance was 0.08%, and the change rate of the solar transmittance was 1.46%.
[0107] [Example 2] The coating film forming dispersion A according to Example 1 was dried in a vacuum to evaporate the medium from the aged liquid, thereby obtaining a powder containing surface-treated infrared-absorbing fine particles according to Example 2. 8% by mass of the surface-treated infrared-absorbing fine particle powder according to Example 1 was mixed with 24% by mass of a polyacrylate-based dispersant and 68% by mass of toluene. The resulting mixture was loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and pulverized and dispersed for 1 hour to obtain a surface-treated infrared-absorbing fine particle dispersion according to Example 2. 26 g of a 40% by mass silica fine particle toluene dispersion was added to 700 g of this infrared-absorbing fine particle dispersion, thereby obtaining an infrared-absorbing fine particle dispersion according to Example 2. The content of silica fine particles in the infrared-absorbing fine particle dispersion powder was 3.2% by mass.
[0108] The infrared absorbing composite microparticles, the infrared absorbing microparticle dispersion, the infrared absorbing microparticle dispersion powder, and the infrared absorbing sheet of Example 2 were obtained by carrying out the same operations as in Example 1, except that the infrared absorbing microparticle dispersion of Example 2 was used, and the evaluations were carried out in the same manner as in Example 1. The production conditions are shown in Table 1, and the evaluation results are shown in Table 2. The toluene dispersion of silica fine particles was obtained by dispersing silica fine particles having an average particle size of 20 nm in a toluene solvent using a collision type high-pressure emulsifier.
[0109] [Example 3] The same operations as in Example 1 were carried out except that 75 g of 20 mass % silica water dispersion was added to 650 g of the aged solution of Example 1, to obtain infrared absorbing composite microparticles, infrared absorbing microparticle dispersion liquid, infrared absorbing microparticle dispersion powder, and infrared absorbing sheet of Example 3, and evaluations were carried out in the same manner as in Example 1. The content of silica microparticles in the infrared absorbing microparticle dispersion powder was 4.1 mass %. The production conditions are shown in Table 1, and the evaluation results are shown in Table 2.
[0110] [Comparative Example 1] 2000g of the coating film forming dispersion A was placed in a beaker, and 1000g of the diluted surface treatment agent a was added dropwise over 5 hours while stirring vigorously with a bladed stirrer. After the dropwise addition of the diluted surface treatment agent a, stirring was continued for 24 hours at a temperature of 20°C to prepare the aged liquid according to Comparative Example 1. Next, the medium was evaporated from the aged liquid by vacuum fluidized drying to obtain a powder containing surface-treated infrared absorbing microparticles according to Comparative Example 1 (surface-treated infrared absorbing microparticle powder). No silica microparticles were contained in the infrared absorbing microparticle dispersion powder.
[0111] The surface-treated infrared absorbing microparticle powder, infrared absorbing microparticle dispersion, infrared absorbing microparticle dispersion powder, and infrared absorbing sheet of Comparative Example 1 were obtained by carrying out the same operations as in Example 1, except that the surface-treated infrared absorbing microparticle powder of Comparative Example 1 was used, and evaluations were carried out in the same manner as in Example 1. The production conditions are shown in Table 1, and the evaluation results are shown in Table 2.
[0112] [Table 1] [Table 2]
Claims
1. The surface of the infrared absorbing particles is Infrared absorbing composite particles coated with a coating film containing one or more selected from a hydrolysis product of a metal chelate compound, a polymer of a hydrolysis product of a metal chelate compound, a hydrolysis product of a metal cyclic oligomer compound, and a polymer of a hydrolysis product of a metal cyclic oligomer compound, The infrared absorbing composite particles have silica fine particles present in one or more locations selected from within the coating film, on the coating film, and near the surface of the infrared absorbing composite particles.
2. 2. The infrared absorbing composite particles according to claim 1, wherein the coating film has a thickness of 0.5 nm or more.
3. 3. The infrared absorbing composite particles according to claim 1, wherein the metal chelate compound or the cyclic metal oligomer compound contains one or more metal elements selected from the group consisting of Al, Zr, Ti, Si and Zn.
4. 4. The infrared absorbing composite particles according to claim 1, wherein the metal chelate compound or the metal cyclic oligomer compound has at least one group selected from the group consisting of an ether bond, an ester bond, an alkoxy group and an acetyl group.
5. 5. The infrared absorbing composite particles according to claim 1 , wherein the infrared absorbing composite particles are infrared absorbing composite tungsten oxide particles represented by a general formula MxWyOz (wherein M is one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, I, and Yb; W is tungsten; O is oxygen; and 0.001≦x / y≦1, 2.0≦z / y≦3.0).
6. 6. The infrared absorbing composite particles according to claim 1, wherein the carbon concentration is from 0.2% by mass to 5.0% by mass.
7. An infrared absorbing microparticle dispersion liquid in which infrared absorbing composite microparticles described in any one of claims 1 to 6 are dispersed in a liquid medium.
8. 8. The infrared absorbing nanoparticle dispersion according to claim 7, wherein the liquid medium is at least one selected from the group consisting of organic solvents, oils and fats, liquid plasticizers, compounds that are polymerized by curing, and water.
9. An infrared absorbing microparticle dispersion in which the infrared absorbing composite microparticles described in any one of claims 1 to 6 are dispersed in a solid resin.
10. 10. The infrared absorbing nanoparticle dispersion according to claim 9, wherein the solid resin is one or more resins selected from the group consisting of fluororesin, PET resin, acrylic resin, polyamide resin, vinyl chloride resin, polycarbonate resin, olefin resin, epoxy resin, and polyimide resin.
11. An infrared absorbing microparticle dispersion which is a dried solid of the infrared absorbing microparticle dispersion liquid described in claim 7 or 8.
Citation Information
Patent Citations
UV and / or ir shielding film, coating material for forming the film and forming method
JP1997176527A
Infrared shielding microparticle, its manufacturing method, infrared shielding microparticle dispersion, infrared shielding element, and infrared shielding base material
JP2008291109A
Near infrared ray shielding highly translucent sheet, and near infrared ray noise shielding material
JP2011133586A
Heat shielding composition, member for solar cell, and solar cell
JP2011181636A
Infrared blocking particle, method for producing the same, infrared blocking particle dispersion using the same, and infrared blocking base
WO2010055570A1